PENGARUH MODEL PROBLEM BASED LEARNING DISERTAI PETA KONSEP TERHADAP MOTIVASI BELAJAR IPA SISWA SMP KELAS VII MATERI PEMANASAN GLOBAL - Muhammad Fiky Mayshandy; I Ketut Mahardika; Aris Singgih Budiarso (Bioilmi: Jurnal Pendidikan, 2021)
The PBL model is a suitable learning model to make students actively involved in learning activities and is supported by media in the form of concept maps to attract student motivation. The purpose of this study was to determine the effect of the application of the PBL model with concept maps on the science learning motivation of seventh grade junior high school students regarding global warming. This research includes experimental research. The results of the study which were tested by statistical independent sample t-test obtained a significance value of 0.000, which means that it is smaller than 0.05, it was decided that H0 was rejected and Ha was accepted. So it can be concluded that there is a significant effect of the application of the PBL model with concept maps on the science learning motivation of junior high school students on global warming material.